Clinical Perception and Treatment Options for Behavioral and Psychological Symptoms of Dementia (BPSD) in Italy - D'Antonio, Fabrizia; Tremolizzo, Lucio; Zuffi, Marta; Pomati, Simone; Farina, Elisabetta; , Sindem BPSD Study Group; Alberoni, Margherita; Amici, Serena; Andrea, Arighi; Baglio, Francesca; Barocco, Federica; Cecilia Bruni, Amalia; et al. (Frontiers in Psychiatry, 2022)
Background: Behavioral and psychological symptoms of dementia (BPSD) have a high prevalence and their presence is associated with a severe impact in terms of social costs. However, dedicated clinical tools or biomarkers to detect these symptoms are lacking. Thus, BPSD management in clinical settings is challenging. Aim of this study was to investigate the perception and the treatment strategies for BPSD in Italian centers working in dementia field. Methods: A multicenter, national survey was developed by BPSD Study Group of the Italian Neurological Society for Dementia (SINDEM). The survey consisted of a semi-structured questionnaire, that was e-mailed to SINDEM members, dementia Centers part of the national network of memory clinics (Centers for Cognitive Deterioration and Dementia (CDCD)) and clinicians working in dementia care settings. The questions were focused on 1) perceived global frequency and relevance of BPSD 2) tools used to assess BPSD 3) pharmacological treatment for psychosis, apathy, agitation, aggression, depression, anxiety, sleep and nutrition disturbances; 4) non-pharmacological treatments; 5) drug side effects. Results: One-hundred-thirty-six cliniciants participated in this study. Seventy-nine participants worked in a CDCD and 57 in other settings. The perceived frequency of BPSD was 74%. BPSD are detected by means of a clinical assessment for 96.3% or a caregiver interview for 97%. For psychosis treatment the first-choice were atypical antipsychotics (83.3%), followed by typical antipsychotic (8.9%) and antidepressants (4.8%). For agitation, atypical antipsychotics were the first-choice treatment in 64% of cases and antidepressants in 16.1%. For aggression, the most used drugs were atypical antipsychotics (82.9%). For anxiety, 55.2% use antidepressants, 17.9% use atypical antipsychotics and 16.9% benzodiazepines. Interestingly, most of the centers apply non-pharmacological treatments for BPSD. Some differences emerged comparing the responses from CDCD and other care settings. Conclusion: The survey results revealed many differences in BPSD perception, treatment options and observed side effect according to the clinical setting. This variability can be explained by the absence of clear guidelines, by differences in patients’ characteristics and by clinical practice based on subjective experience. These results suggest that producing guidelines for the pharmacological treatment of BPSD is a major need